Siebenstorch Roman - Pludra, Benno 1925-2014 (Tabu-Verl., 1995)
Storks come to Maika's garden for the seventh year, but this time there are three baby storks too. One of them is quite different, doesn't learn to fly and seems to want to stay with Maika.
Lizenz des Kinderbuch-Verl., Berlin
Keywords: Storks -- Fiction; Weißer Storch; Jungtiere; Aufzucht; Außenseiter; Hilfeleistung; Kinderbuch